A DNAzyme-mediated logic gate system based on Ag(i)–cysteine. Issue 20 (11th August 2020) - Zhang, Xun; Zhang, Qiang; Liu, Yuan; Wei, Xiaopeng
Abstract : A switchable logic circuit which can represent three kinds of logical operations by adjusting concentration of silver ion and cysteine (Cys) based on E6 and Ag10c DNAzyme was developed. Abstract : Ag + plays an important role in DNA mismatch technology due to its affinity for cytosine in DNA. This article introduces a strategy to control the enzyme digesting reaction by utilizing the characteristics of C–Ag + –C mismatches, effectively regulating and controlling the activity of the E6 DNAzyme via changing the structure of its conservative domain. We designed a series of basic logic gates, a "Yes" Gate, an "Or" Gate and an "Inhibit" Gate. Cysteine (Cys) can combine with Ag +, reducing the concentration of Ag + in solution, thus restraining the C–Ag + –C mismatch effect. Based on this principle, we regard Cys as a threshold, and designed a type of "Inhibit" Gate based on input quantity by changing the concentration of Ag +, thus generating different statues of logic output. On this basis, the E6 DNAzyme and Ag10c DNAzyme can be integrated into new systems with the function of logic operation circuit based on the control of Ag + concentration in solution. This system could represent three different states of logical expression by controlling the quantity of Ag + and Cys.